Narrative Transmedia - Peña-Acuña, Beatriz (IntechOpen, 2020)
The transmedia narrative is a format that will renew interest in reading and stories, and also allow innovation in various educational fields, if you know how to apply and combine with innovative teaching methodologies that support and encourage play. The transmedia narrative offers a new educational and communicative landscape in a society that is discovering the possibilities offered by platforms and new digital narrative formats. This book is written by creative authors and contains many examples of innovation through transmedia narrative.